Computer control of an HF chirp radar - Griggs, Desmond Bryan (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1991)
This thesis describes the interfacing of an IBM compatible microcomputer to a BR Communications chirp sounder. The need for this is twofold: Firstly for control of the sounder including automatic scheduling of operations, and secondly for data capture. A signal processing card inside the computer performs a Fast Fourier Transform on the sampled data from two phase matched receivers. The transformed data is then transferred to the host computer for further processing, display and storage on hard disk or magnetic tape, all in real time. Critical timing functions are provided by another card in the microcomputer, the timing controller. Built by the author, the design and operation of this sub-system is discussed in detail. Additional circuitry is required to perform antenna and filter switching, and a possible design thereof is also presented by the author. The completed system, comprising the chirp sounder, the PC environment, and the signal switching circuitry, has a dual purpose. It can operate as either a meteor radar, using a fixed frequency (currently 27,99 MHz), or as an advanced chirp ionosonde allowing frequency sweeps from 1,6 to 30 MHz. In the latter case fixed frequency doppler soundings are also possible. Examples of data recorded in the various modes are given.
Keywords: Radar; Radar meteorology; Computerized instruments; Ionosondes